A study to measure the level of customer satisfaction towards product quality produced by Koperasi Pekebun Kecil Daerah Segamat Berhad ( Kopedas Berhad ) / Roslina Abu Bakar - Abu Bakar, Roslina (2011)
This study is designed to study the level of customer satisfaction towards product quality produced by Koperasi Pekebun Kecil Daerah Segamat Berhad (Kopedas Berhad). The research used the product quality dimensions. There are four (4) dimensions in product quality which are product performances, service ability, aesthetic and perceived. This dimension will be used to identify customer satisfaction towards product quality produced by Kopedas Berhad. In this study, the methods used are questionnaire to identify the relevant information regarding the study on customer satisfaction towards product quality produced by Kopedas Berhad. Researcher also used secondary data such as journals, references books, previous thesis and internal data. Researcher also used the close-ended question and open ended question to obtain the information. The findings from the study found that product quality is involved to customer satisfaction towards product quality produced by Kopedas Berhad.